THE ENIGMATIC POWER OF 142857 IN THE ANCIENT EGYPTIAN PYRAMIDS - Tian Bin; Wang Fang; Ren Yifan (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2023)
Ever since the enigmatic number 142857 was unearthed within the archaeological context of the ancient Egyptian pyramids, it has captivated the attention of mathematicians and scientists worldwide. Numerous studies have been conducted in an attempt to establish a direct or indirect connection between this number and the pyramids, yet no conclusive research findings have emerged thus far. Nevertheless, based on the continuous research of ancient civilizations, characters, and masterpieces, the calculation method of the line segment and the relationship between polygons and numbers are discovered in the exploration of polygons, right triangles, multiplication tables, and the mathematical constant ?. These discoveries have unveiled a fascinating string of numbers that can potentially reveal that ancient Egyptian pyramids were designed and constructed using the mathematical approach rooted in the application of isosceles right triangles, with "5" and "7" as representative values, rather than simply representing the cyclic meaning. Furthermore, they have illuminated the profound wisdom possessed by the ancient Egyptians, affirming that the pyramids stand as a testament to the advanced development of ancient mathematics. This discovery not only represents a cognitive advancement in the study of ancient Egyptian archaeology and history but also holds immense importance in the broader realm of ancient mathematics and its impact on the development of modern mathematics.